Impact of motivational factors on job performance of universities’ library professionals in Peshawar, Pakistan - Shah, Farooq; Ismail, Muhammad; Salman, Muhammad (IJoLIS, 2025)
Purpose: The major purpose of this study is to explore the impact of motivational factors on job performance of university library professionals in Peshawar, Khyber Pakhtunkhwa, Pakistan. Design/methodology/approach: The study used quantitative research approach with survey research designs. The data was collected through a structured questionnaire which was administered to all 69 library professionals working in the university libraries in Peshawar. This study determined motivational factors such as growth, achievement, work itself, job security, advancement, recognition, money, relationship with supervision, working conditions, and university policy. Research limitations: The paper is limited to library professionals working in the university libraries in district Peshawar. Originality value: Literature review indicated that only few of the studies have been conducted on impact of motivational factors on job performance of university library professionals in Pakistan. As yet there have been no such studies that measured various motivational factors that impact the job performance of university library professionals in Peshawar. Thus this is one of the unique studies on the topic. Key findings: Results indicated that the level of job performance of library professionals was good, but the motivational factors influenced their job performance. Growth, achievement, work itself, recognition, and job security were found as the most significant factors that motivate library professionals and have a significant relationship with job performance. Money was found to be a moderate factor that motivates library professionals and has a moderate relationship with job performance. The relationship with supervision, working conditions, and university policy were weak factors that motivated library professionals and have a weak relationship with job performance. Practical implications: The findings and recommendations made in this study will help librarians and university administration to improve their style of management and efficiently motivate library professionals towards better job performance and service delivery. Contribution to knowledge: Overall, the study contributes to understanding the multidimensional nature of motivation and its impact on individual and organizational success.